Aplicación de sistemas embebidos en la construcción de robots móviles. El caso del club de robótica de la Universidad Técnica de Cotopaxi. - Sosa Valverde, Marco Antonio (2020)
This project shows the design, construction and validation of a micro-controlled application in mobile robotics called "BRICK". It aims to program a robot through an IDE (integrated development environment) by using free software and operated by a computer. In this research confirmation, the importance of the use of electronics in embedded systems is exposed. It revealed that this type of systems are flexible and can be adapted to a general or specific proposal based on the use of a methodology in mechatronic projects. They are ran by signals controlled in a touch screen or other different methods such as infrared rays or bluetooth, commanded from a Smartphone and giving orders according to the needs of the user. These patterns activate the operation of the devices that were integrated in the robot programming based on algorithms communication through wireless signals.